2013
DOI: 10.3904/kjim.2013.28.5.547
|View full text |Cite
|
Sign up to set email alerts
|

Impact of family history on the presentation and clinical outcomes of coronary heart disease: data from the Korea Acute Myocardial Infarction Registry

Abstract: Background/AimsFamily history (FHx) of coronary heart disease (CHD) is a well-known risk factor for CHD. However, the prognostic implication of FHx has not been established clearly in patients with acute myocardial infarction (AMI).MethodsIn total, 11,612 patients (8,132 males [70%], age 63 ± 13 years) with first-onset AMI between November 2005 and June 2008 in a nationwide, prospective, multicenter, online registry (the Korea AMI Registry) were analyzed. Clinical characteristics and outcomes (cardiac death an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
2
8
0
1
Order By: Relevance
“…17 A study in South Korea showed that patients with a family history of ischaemic heart disease were younger and more likely to be male. 18 In the present study, having a family history of ischaemic heart disease was associated with more cardiovascular events (p=0.035).…”
Section: Discussionsupporting
confidence: 46%
“…17 A study in South Korea showed that patients with a family history of ischaemic heart disease were younger and more likely to be male. 18 In the present study, having a family history of ischaemic heart disease was associated with more cardiovascular events (p=0.035).…”
Section: Discussionsupporting
confidence: 46%
“…Gender differences in the impact of family history on IHD risk have been controversial. In a multivariate analysis of traditional Framingham risk factors, family history was predictive of major adverse CVD events in women but there was no significant increased risk in men 47 . A larger study showed gender differences as well.…”
Section: Non-framingham Risk Factorsmentioning
confidence: 89%
“…Genetic factors play a significant role in the occurrence and progression of many diseases, such as coronary heart disease ( 37 , 38 ), diabetes ( 39 ) and diabetes insipidus ( 40 ). However, it is very difficult to screen causative genes through pedigrees, and there is no unified and standardized method.…”
Section: Discussionmentioning
confidence: 99%